2014
DOI: 10.1158/2159-8290.cd-13-0346
|View full text |Cite
|
Sign up to set email alerts
|

RapidCaP, a Novel GEM Model for Metastatic Prostate Cancer Analysis and Therapy, Reveals Myc as a Driver of Pten-Mutant Metastasis

Abstract: Genetically engineered mouse (GEM) models are a pillar of functional cancer research. Here, we developed RapidCaP, a GEM modeling system that uses surgical injection for viral gene delivery to the prostate. We show that in Pten defi ciency, loss of p53 suffi ces to trigger metastasis to distant sites at greater than 50% penetrance by four months, consistent with results from human prostate cancer genome analysis. Live bioluminescence tracking showed that endogenous primary and metastatic disease responds to ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(131 citation statements)
references
References 44 publications
8
117
1
Order By: Relevance
“…Therefore, we are aware that we need to confirm the effect of metformin on the formation of metastasis in another mouse model. Thus, it would be interesting to test the effects of metformin in the "RapidCaP" model recently described by Cho and colleagues (60). In this new model, unlike our study, mice develop metastasis from mouse prostate tumors.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, we are aware that we need to confirm the effect of metformin on the formation of metastasis in another mouse model. Thus, it would be interesting to test the effects of metformin in the "RapidCaP" model recently described by Cho and colleagues (60). In this new model, unlike our study, mice develop metastasis from mouse prostate tumors.…”
Section: Discussionmentioning
confidence: 83%
“…Since viral-Cre infection of the lung, prostate, bladder, and muscle can initiate cancer in adult tissues (Jackson et al 2001;Kirsch et al 2007;Puzio-Kuter et al 2009;Cho et al 2014), we considered how best to deliver viral-Cre to the pancreas without infecting other cells within the peritoneal cavity. To specifically initiate recombination in cells within the adult pancreas while keeping the virus contained within the target organ, we used retrograde pancreatic ductal injection.…”
Section: Resultsmentioning
confidence: 99%
“…Given the ability of BET inhibitors to repress c-MYC expression in a range of tumor types (7,9,32,33) and the importance of c-MYC in promoting the initiation and progression of colon cancer, we sought to determine the effect of BET inhibitors on the growth of colorectal cancer cells and the role of c-MYC in mediating these effects. By analyzing a panel of 20 colon cancer cell lines, we found that sensitivity to JQ1 was significantly associated with the magnitude of repression of c-MYC.…”
Section: Introductionmentioning
confidence: 99%